Analisis Kontribusi Ibnu Qayyim Al-Jauziyyah Dalam Filsafat Ekonomi Islam - Syamsuri Syamsuri; Sabila Rosyida (Islamic Economics Journal, 2018)
Scientific activity, both in theory and scholarly thinking, is basically born from the ideals of a systematic, rational, logical and empirical fi gures. In the 13th century a great philosopher named Ibn Qayyim contributed in building the foundations of Islamic economic philosophy which discussed the issues of human concept, wealth and poverty, ownership, usury and even the concept of money. Although the pa; ern of economic thinking infl uenced by his teacher is Ibn Taymiyah. However, the brilliant idea of Ibn Qayyim in giving the basic concept of Islamic economics is very worthy to be reviewed. Thus, this article a; empts to analyze the extent of Ibnu Qayyim al-Jauziyyah’s contribution to the philosophy of Islamic economics. Using an analytical descriptive method with a qualitative approach that describes the contribution of thought Ibn Qayyim in economic philosophy then theories are analyzed inductively. This article concludes that Ibn Qayyim’s economic thought is based on faith and Tauhid, besides that he also does not distinguish between religion and economy, including the relevance between obedience to the acquisition of sustenance, the world and the whole to be benefi ted by humans with economic activities, dividing usury to nasi’ah and fadl, transition of ownership in a state of urgency, the state is entitled to take individual ownership if it is more beneficial for maslahah umah.